THE PERSON BEHIND THE GREATNESS: ALEXANDER'S INNER WORLD AND EXPERIENCES (Western European Journal of Historical Events and Social Science, 2025)
This article examines the life and achievements of Alexander the Great, the renowned commander who lived in the 4th century BC and gained worldwide fame. It analyzes his childhood, military campaigns, political marriages, and personal qualities based on historical sources. The article explores Alexander's role in unifying the East and West, his marriage to Roxana, and the resulting political connections with Sogdiana. Additionally, it discusses various historical and conspiratorial theories regarding Alexander's death. The article presents a comprehensive view of Alexander's personality through diverse sources and perspectives.